Hybridizing MoS2 and C60 via a van der Waals heterostructure toward synergistically enhanced visible light photocatalytic hydrogen production activity. (3rd May 2018) - Guan, Jian; Wu, Jianhua; Jiang, Daochuan; Zhu, Xianjun; Guan, Runnan; Lei, Xunyong; Du, Pingwu; Zeng, Hualing; Yang, Shangfeng
Abstract: Molybdenum disulfide (MoS2 ) as a representative transition-metal dichalcogenide (TMD) has been extensively used as a noble-metal-free cocatalyst for photocatalytic hydrogen (H2 ) production, but suffers from poor photocatalytic activity due to the catalytic inactivity of its basal plane. Herein, by bounding another metal-free cocatalyst, C60, with MoS2, we report the first MoS2 -C60 hybrid featuring a van der Waals heterostructure prepared via a facile and eco-friendly solid-state mechanochemical route. C60 bounding onto the edge of MoS2 nanosheets leads to the decreases of both the number of layers and the size of MoS2 nanosheets, as well as a negative shift of the conduction band minimum along with a positive shift of valance band maximum relative to the bulk MoS2 and MoS2 ball-milled without C60 (MoS2 -BM). Under the optimized weight ratio of MoS2 :C60 (1:1) in the raw mixture subject to ball-milling, MoS2 -C60 hybrid containing 2.8 wt% C60 shows an exceptional visible light photocatalytic H2 production rate of 6.89 mmol h −1 g −1 in the presence of a photosensitizer Eosin Y (EY), which is significantly enhanced relative to the bulk MoS2 and pristine C60, both of which show almost no photocatalytic H2 activity. Thus, the synergistic enhancement of photocatalytic activities of both MoS2 and C60 is revealed. Graphical abstract: MoS2 and C60 as two noble-metal-free cocatalysts were hybridized for the first time via a facile and eco-friendly solid-state mechanochemical route, affording a novel van der Waals heterostructure of 2D TMD and 0D fullerene. MoS2 -C60 hybrid shows a visible light photocatalytic H2 production rate of 6.89 mmol h −1 g −1 in the presence of a photosensitizer Eosin Y, which is significantly enhanced relative to those of the bulk MoS2 and pristine C60, revealing the synergistic enhancement of their photocatalytic activities. Highlights: The first MoS2 -C60 hybrid is prepared via a solid-state mechanochemical route. C60 bounding leads to the decreases of the thickness and size of MoS2 nanosheets. MoS2 -C60 hybrid shows a visible light H2 production rate of 6.89 mmol h −1 g −1 . C60 bounding results in the fast photoinduced electron transfer from MoS2 to C60 .